2016
DOI: 10.1097/mcg.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fecal Microbiota and Fecal Metabolome in Symptomatic Uncomplicated Diverticular Disease of the Colon

Abstract: SUDD and AD do not show colonic bacterial overgrowth, but a significant difference in the levels of fecal A. muciniphila was observed. Moreover, increasing expression of some metabolites as expression of different AD and SUDD metabolic activity was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
108
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 15 publications
0
108
0
1
Order By: Relevance
“…38 Existing metabolomics studies of humans with expansion of mucolytic organisms such as Akkermansia have not shown consistent metabolite signatures. 39,40 Although the Tsyn and Cosmc SNPs described here were not found to be associated with IBD in a large meta-analysis of Immunochip data, the SNP-associated changes in the colonic mucosal microbiome are reminiscent of changes seen in IBD patients. 41 In particular, Cosmc minor allele carriers had changes paralleling IBD including increased Enterobacteriaceae, Veillonella parvula, and H. parainfluenzae.…”
Section: Discussionmentioning
confidence: 98%
“…38 Existing metabolomics studies of humans with expansion of mucolytic organisms such as Akkermansia have not shown consistent metabolite signatures. 39,40 Although the Tsyn and Cosmc SNPs described here were not found to be associated with IBD in a large meta-analysis of Immunochip data, the SNP-associated changes in the colonic mucosal microbiome are reminiscent of changes seen in IBD patients. 41 In particular, Cosmc minor allele carriers had changes paralleling IBD including increased Enterobacteriaceae, Veillonella parvula, and H. parainfluenzae.…”
Section: Discussionmentioning
confidence: 98%
“…Gas chromatography-mass spectrometry (GC-MS) and liquid chromatography-mass spectrometry (LC-MS) are widely implemented for the detection of metabolites in stool samples for disease research (15,16). Metabolome profiling is frequently conducted in conjunction with gut microbiome studies to study the microbiome's metabolic potential (17,18).…”
mentioning
confidence: 99%
“…(15)(16)(17)(18)(19)(20)(21) Global geographical differences in the intestinal microbial community also correspond to differences in the prevalence of diverticular disease. (21)(22)(23) Several studies have examined the intestinal microbial composition in patients with symptomatic asymptomatic diverticular disease (24)(25)(26) and in asymptomatic diverticulosis. (27,28) Only two small studies have explored the intestinal microbiota in patients with diverticulitis.…”
Section: Introductionmentioning
confidence: 99%
“…adjusted for multiple comparisons. Nonetheless, a supervised clustering approach was able to distinguish diverticulitis cases from diverticulosis controls 80% of the time based on the relative abundance of the 7 genera.A few studies have examined the intestinal microbiota in patients with symptomatic asymptomatic diverticular disease (SUDD) (24,26). SUDD is an incompletely understood condition generally defined as the presence of abdominal symptoms in patients with diverticulosis and gastrointestinal symptoms in the absence of evidence of diverticulitis.Barbara et al, compared the fecal and mucosal microbiota in 14 controls without diverticulosis, 16 patients with asymptomatic diverticulosis and 8 patients with SUDD.…”
mentioning
confidence: 99%